Operation and Control of Electric Energy Processing Systems - Momoh J. James; Mili L. Lamine (Hoboken, IEEE Press, 2010)
Focusing on the dynamic modeling and control of interdependent communications and electric energy systems, micro-electro-mechanical systems (MEMS), and the interdisciplinary education component of the EPNES (Electric Power Networks Efficiency and Security) initiative, Operation and Control of Electric Energy Processing Systems provides a working knowledge of, as well as cutting-edge developments in, electric power systems theory and applications. The book begins with an introduction to the EPNES initiative, and then investigates several dynamical models in fault tolerant operation and control of energy processing systems. Intelligent power routers for distributed coordination of electric energy processing networks are developed. Next, the book addresses the design of power circuit breakers, using an array of small MEMS switches together with diodes for faster operation and smaller equipment size aimed at reducing the vulnerability of a power system to faults. A GIS-based market simulation studies for power systems education is then developed. Finally, the book employs a social-sciences approach to help understand the development and use of distributed generation technologies-small-scale generators that produce power near their loads-in the electric power system. Operation and Control of Electric Energy Processing Systems can be used both as a book for teaching graduate courses and as a handbook that provides state-of-the-art knowledge to engineers and researchers working worldwide in interdisciplinary areas such as control, power systems, economics, environment, and social sciences. It will also appeal to policy makers as well as executives and engineers of electric utilities.